Copper-iron bimetallic MOFs material, preparation method and application thereof, and method for preparing N-substituted pyrrole compound
By using copper-iron bimetallic MOFs materials as catalysts, the problems of low selectivity of N-substituted pyrrole compounds and expensive catalysts in the prior art are solved, and efficient and selective preparation of pyrrole compounds is achieved, and the preparation cost and environmental risks are reduced.
Patent Information
- Application Number
- CN202311146000.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-06
AI Technical Summary
In the prior art, the selectivity of N-substituted pyrrole compounds or the catalyst requires the use of expensive metals, resulting in high production costs and insufficient environmental protection performance.
Copper-iron bimetallic MOFs material is used as a catalyst, which only contains L acid sites and hybridizes with the bimetal center through coordination bonds to form a three-dimensional network structure, which is used to catalyze the reaction of furan compounds and amine compounds under mild conditions.
The efficient preparation of N-substituted pyrrole compounds is achieved, with high reaction efficiency and high selectivity, avoiding the generation of by-products and reducing the risk of corrosion to the equipment.
Smart Images

Figure CN119570045A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal organic framework materials, and in particular to a copper-iron bimetallic MOFs material and a preparation method and application thereof, and a method for preparing an N-substituted pyrrole compound. Background Art
[0002] Over the past few decades, the world has become increasingly dependent on petroleum as the main source of chemicals and energy. Due to the increasing industrial demand and the decreasing reserves of petroleum resources, the conversion strategies for preparing fine chemicals and biofuels from native biomass have attracted widespread attention from scientists. Lignocellulose can be easily converted into platform compounds containing specific functional groups, including furans and benzene rings, which provides a good entry point for downstream processing. Although in recent years, researchers have made significant efforts to develop new catalytic routes and processes to convert platform compounds into various high-density biosynthetic fuels, the development of new transformations that are orthogonal or complementary to existing green and sustainable chemical synthesis methods remains a very important industrial topic.
[0003] Nitrogen heterocycles, especially functionalized pyrroles, are important structural units of a large number of naturally occurring and pharmacologically active molecules. They are widely used in the core structures of bioactive substances such as vitamins, anticancer drugs, and antibacterial drugs. Patent document CN103288701A discloses a 1,5-diaryl pyrrole derivative, which is prepared by using 1,4-dicarbonyl compounds and amine compounds under the catalytic action of protonic acids, and the yields of most embodiments are around 40-60%. The main approach to traditional N-substituted pyrroles usually uses substituted ketones, aldehydes, or amines as substrates, most of which come from petrochemical resources, and the yield of the reaction is low. It is more important to explore the construction of pyrrole derivatives based on biomass.
[0004] The heterogeneous catalytic dehydrogenative coupling reaction of bio-secondary alcohols with amino alcohols pioneered in the literature [Nat. Chem. 2013, 5, 140-144; Catal. Sci. Technol. 2014, 4, 4188-4192] has become an important method for constructing pyrrole skeletons. Although the reaction yield is high, the high separation and recovery cost and potential toxicity of iridium species still pose challenges to the establishment of a greener and more sustainable synthesis method.
[0005] Recently, it has been reported that the use of solid acid H-type zeolite Y catalyst can realize the condensation of aromatic amines and furans to prepare pyrrole under mild conditions [ACS Catal. 2017, 7, 959.]. Studies have confirmed that the Bronsted acid site (protonic acid) is the key catalytic site of the catalyst, and the reaction undergoes the classic PaalKnorr reaction pathway. CN111574424B reports a method for preparing N-aryl pyrrole compounds using a catalyst containing a Lewis acid, wherein the catalyst is synthesized by a sol-gel method, with a mesoporous molecular sieve SBA15 as a carrier, and Hf is loaded as a core metal element. However, there is a problem of uneven distribution of metal elements and easy leaching. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of low selectivity of N-substituted pyrrole compound products or the need for expensive metals in the catalyst in the prior art, and to provide a copper-iron bimetallic MOFs material and a preparation method thereof and an application and method for preparing N-substituted pyrrole compounds. The copper-iron bimetallic MOFs material contains only L acid sites and is used as a catalyst for synthesizing N-substituted pyrrole compounds. It reacts under mild conditions and has outstanding characteristics such as high reaction efficiency and high yield of furan compounds and amine compounds, thereby achieving high reaction efficiency and high product yield.
[0007] In order to achieve the above object, the first aspect of the present invention provides a copper-iron bimetallic MOFs material, the copper-iron bimetallic MOFs material comprising:
[0008] A bimetallic center formed by Fe and Cu containing two or more valence states; and
[0009] Organic ligands that hybridize with the bimetallic center through coordination bonds to form a three-dimensional network structure crystal;
[0010] The copper-iron bimetallic MOFs material contains only L acid, and the amount of L acid is 100-600 μmol·g -1 .
[0011] The second aspect of the present invention provides a method for preparing the copper-iron bimetallic MOFs material of the present invention, the method comprising the following steps:
[0012] S1, dissolving the organic ligand and the Cu salt in a solvent, crystallizing, separating, and first drying to obtain a Cu-based MOFs material formed by Cu and the organic ligand;
[0013] S2, contacting the Cu-based MOFs material in step S1 with a water-alcohol mixture containing Fe element and Fe salt; separating and performing a second drying to obtain the copper-iron bimetallic MOFs material.
[0014] The third aspect of the present invention provides an application of the copper-iron bimetallic MOFs material of the present invention in the synthesis of pyrrole compounds.
[0015] A fourth aspect of the present invention provides a method for preparing an N-substituted pyrrole compound, the method comprising:
[0016] In the presence of a liquid diluent, a furan compound and an amine compound are contacted with a catalyst; the catalyst contains the copper-iron bimetallic MOFs material of the present invention.
[0017] Through the above technical solution, the copper-iron bimetallic MOFs material of the present invention, both metals are bonded to organic ligands, and due to the interaction of the two metals, the metal valence state changes, forming more empty coordination sites, and the copper-iron bimetallic MOFs material contains only L acid (Lewis acid) sites. According to a preferred embodiment of the present invention, the crystal surface of the copper-iron bimetallic MOFs material presents a regular rough morphology or an uneven morphology; more preferably, the rough morphology covers the crystal surface of the copper-iron bimetallic MOFs material in a network shape; or the rough morphology covers the crystal surface of the copper-iron bimetallic MOFs material in the form of particles.
[0018] The copper-iron bimetallic MOFs material of the present invention is used for synthesizing pyrrole compounds (such as N-substituted pyrrole compounds) with high reaction efficiency and high selectivity.
[0019] In the prior art, the traditional catalytic method for preparing N-substituted pyrrole compounds uses B acid (protonic acid) as a catalyst, and this method is easily affected by the presence or absence of water in the reaction system. In the present invention, the method for preparing N-substituted pyrrole compounds uses the copper-iron bimetallic MOFs material of the present invention as a catalyst. Since the copper-iron bimetallic MOFs material only contains L acid sites, it can catalytically convert furan compounds and amine compounds to prepare N-substituted pyrrole compounds under mild reaction conditions, and prevent the generation of by-products such as 3-methyl-2-cyclopentenone. The method has high selectivity; and since a catalytic material containing Lewis acid is used, it is not easy to corrode the equipment at high temperatures; at the same time, since the reaction conditions are mild, the structure of the copper-iron bimetallic MOFs material will not be damaged, and thus it also provides a new idea for the application of MOFs in catalysis.
[0020] The preparation method of the copper-iron bimetallic MOFs material of the present invention utilizes the idea of self-reduction of multivalent transition metals and creatively adds elemental iron. Under the action of elemental iron, the modified solution has reducing properties, so that the effective reducing components can act to a greater extent. In addition to the reducing effect, the metallic iron can also provide more vacant sites to increase the acid content of the material, so that the multivalent copper-iron bimetallic MOFs material contains only L acid. In the copper-iron bimetallic MOFs material of the present invention, the metal ions and carboxylic acid ligands form a binuclear metal paddle wheel structure at the node, and the coordinated water molecules are easily removed during the preparation process to form an open metal center as a catalytic center. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a scanning electron microscope (SEM) image of Cu-BTC in Example 1;
[0022] Figure 2 This is a scanning electron microscope (SEM) image of the Fe-Cu-BTC obtained in Example 1;
[0023] Figure 3 is a scanning electron microscope (SEM) image of Fe-Cu-BTC-8 obtained in Example 8;
[0024] FIG4(a) is an X-ray photoelectron spectrum (XPS) of Cu 2p3 / 2 of Cu-BTC and Fe-Cu-BTC obtained in Example 1; FIG4(b) is an X-ray photoelectron spectrum (XPS) of Fe 2p of Cu-BTC and Fe-Cu-BTC obtained in Example 1;
[0025] Figure 5 The pyridine desorption infrared (Py-FTIR) images of Cu-BTC and Fe-Cu-BTC obtained in Example 1;
[0026] Figure 6 The XRD diagrams of Cu-BTC and Fe-Cu-BTC obtained in Example 1 are shown. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] In the present invention, MOFs materials refer to metal organic framework materials or metal organic skeleton materials.
[0029] In the present invention, the metal center refers to the metal ion used to form a coordination complex in the MOFs material.
[0030] The first aspect of the present invention provides a copper-iron bimetallic MOFs material, the copper-iron bimetallic MOFs material comprising:
[0031] A bimetallic center formed by Fe and Cu containing two or more valence states; and
[0032] Organic ligands that hybridize with the bimetallic center through coordination bonds to form a three-dimensional network structure crystal;
[0033] The copper-iron bimetallic MOFs material contains only L acid and the amount of L acid is 100-600 μmol·g -1 Both metals form bonds with organic ligands, and due to the interaction between the two metals, the metal valence state changes, forming more empty coordination sites, and the copper-iron bimetallic MOFs material contains only L acid (Lewis acid) sites.
[0034] In the present invention, the total acid content in the copper-iron bimetallic MOFs material can be selected in a wide range. According to a preferred embodiment of the present invention, the L acid content in the bimetallic MOFs material is 150-400 μmol·g -1 .
[0035] In the present invention, the types of the organic ligands can be selected from a wide range. According to a preferred embodiment of the present invention, the organic ligand is selected from at least one of trimesic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 4,4,4-tris(N,N-di(4-carboxyphenyl)-amino)triphenylamine, 3,3,5,5-biphenyltetracarboxylic acid, imidazole, 2-methylimidazole, 2-nitroimidazole and 2-nitroimidazole derivatives; preferably at least one of trimesic acid and terephthalic acid.
[0036] According to a preferred embodiment of the present invention, in the copper-iron bimetallic MOFs material, the node metal Cu has two valence states, and preferably, the molar ratio of divalent Cu to monovalent copper is 0.01-5.
[0037] According to a preferred embodiment of the present invention, the molar ratio of metal Cu to metal Fe is (1-200):1, preferably (1-80):1.
[0038] In the present invention, the molar ratio of the organic ligand to the metal Cu can be selected in a wide range. According to a preferred embodiment of the present invention, the molar ratio of the metal Cu to the organic ligand is 0.1-10.
[0039] According to a preferred embodiment of the present invention, the copper-iron bimetallic MOFs material crystal is a polyhedral structure.
[0040] According to a preferred embodiment of the present invention, the copper-iron bimetallic MOFs material has a crystal size of 5-20 μm.
[0041] According to a preferred embodiment of the present invention, the crystal surface of the copper-iron bimetallic MOFs material presents a regularly rough morphology or an uneven morphology, and preferably, the rough morphology covers the crystal surface of the copper-iron bimetallic MOFs material in a network shape; or the rough morphology covers the crystal surface of the copper-iron bimetallic MOFs material in the form of particles.
[0042] The copper-iron bimetallic MOFs materials having the aforementioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. With respect to the present invention, according to a preferred embodiment of the present invention, the second aspect of the present invention provides a method for preparing the copper-iron bimetallic MOFs material of the present invention, and the method comprises the following steps:
[0043] S1, dissolving the organic ligand and the Cu salt in a solvent, crystallizing, separating, and first drying to obtain a Cu-based MOFs material formed by Cu and the organic ligand;
[0044] S2, contacting the Cu-based MOFs material in step S1 with a water-alcohol mixture containing Fe element and Fe salt; separating and performing a second drying to obtain the copper-iron bimetallic MOFs material.
[0045] The preparation method of the copper-iron bimetallic MOFs material of the present invention utilizes the idea of self-reduction of multivalent transition metals and creatively adds elemental iron. Under the action of elemental iron, the modified solution has reducing properties, so that the effective reducing components can act to a greater extent. In addition to the reducing effect, the metallic iron can also provide more vacant sites to increase the acid content of the material, so that the multivalent copper-iron bimetallic MOFs material contains only L acid. In the copper-iron bimetallic MOFs material of the present invention, the metal ions and the carboxylic acid ligands form a binuclear metal paddle wheel structure at the node, and the coordinated water molecules are easily removed during the preparation process to form an open metal center as a catalytic center.
[0046] In the present invention, in step S1, the organic ligand and the Cu salt can be dissolved in a solvent to obtain a solution containing the organic ligand and a solution containing the Cu salt, respectively, and then the solution containing the organic ligand and the solution containing the Cu salt are mixed and reacted to obtain a Cu-based MOFs material.
[0047] In the present invention, in step S1, the range of crystallization conditions is relatively wide. According to a preferred embodiment of the present invention, the crystallization conditions include: a crystallization temperature of 30-150°C, preferably 60-110°C; the reaction time can be reasonably determined according to actual needs, preferably, the crystallization time is 3-24h, preferably 10-20h.
[0048] In the present invention, in step S1, the first drying condition has a wide range of optional options. According to a preferred embodiment of the present invention, the drying conditions include: a drying temperature of 70-200°C, and the drying time can be reasonably determined according to actual needs, and the drying time is 2-48h; preferably, drying is performed in steps, and the first step drying conditions include: a temperature of 70-100°C and a time of 1-24h; the second step drying conditions include: a temperature of 120-200°C and a time of 1-24h.
[0049] In the present invention, in step S2, the contact conditions have a wide range of optional contact conditions. According to a preferred embodiment of the present invention, the contact conditions include: a contact temperature of 30-150°C, preferably 50-90°C; the contact time can be reasonably determined according to actual needs, and the contact time is 3-24h, preferably 3-10h.
[0050] In the present invention, the Cu salt is at least one selected from soluble salts of metal Cu.
[0051] In the present invention, the Fe salt is at least one selected from soluble salts of metallic Fe.
[0052] In the present invention, in step S1, the range of solvents available is relatively wide. According to a preferred embodiment of the present invention, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, triethylamine, hydrofluoric acid, tetrahydrofuran, methanol, ethanol and deionized water.
[0053] In step S2, in the water-alcohol mixture, the alcohol is selected from C1-C5 monohydric alcohol or polyhydric alcohol, preferably at least one of methanol, ethanol, propanol and ethylene glycol.
[0054] In the present invention, the crystal surface of the copper-iron bimetallic MOFs material presents a regular rough morphology or an uneven morphology; the rough morphology covers the crystal surface of the copper-iron bimetallic MOFs material in a network shape; or the rough morphology covers the crystal surface of the copper-iron bimetallic MOFs material in particles. According to the selection of anions in the organic ligand and the salt containing the second metal, the crystal surface morphology of the copper-iron bimetallic MOFs material can be regulated. According to a preferred embodiment of the present invention, in step S1, the organic ligand is selected from trimesic acid and / or terephthalic acid; in step S2, in the Fe salt, the anion is selected from at least one of chloride ion and sulfate ion.
[0055] In the present invention, in step S1, the ratio of the amount of solvent to the Cu salt can be selected in a wide range. According to a preferred embodiment of the present invention, the ratio of the amount of solvent to the salt containing the first metal is 5-100 mL solvent / 1.0 g Cu salt.
[0056] According to a preferred embodiment of the present invention, in step S2, the molar ratio of elemental Fe to soluble Fe salt is 1:0.1-10.
[0057] According to a preferred embodiment of the present invention, in step S2, the dosage ratio of the Fe salt is 5-200 mL solvent / 1.0 g.
[0058] The third aspect of the present invention provides an application of the copper-iron bimetallic MOFs material of the present invention in the synthesis of pyrrole compounds. The copper-iron bimetallic MOFs material of the present invention is used to synthesize pyrrole compounds (such as N-substituted pyrrole compounds) with high reaction efficiency and high selectivity.
[0059] A fourth aspect of the present invention provides a method for preparing an N-substituted pyrrole compound, the method comprising:
[0060] In the presence of a liquid diluent, a furan compound and an amine compound are contacted with a catalyst; the catalyst contains the copper-iron bimetallic MOFs material of the present invention. The copper-iron bimetallic MOFs material of the present invention is used as a catalyst. Since the copper-iron bimetallic MOFs material has more L acid sites, it can catalytically convert furan compounds and amine compounds to prepare N-substituted pyrrole compounds under mild reaction conditions, and prevent the generation of by-products (such as 3-methyl-2-cyclopentenone). The method has high selectivity; and since a Lewis acid-containing catalytic material is used, it is not easy to corrode the equipment at high temperatures; at the same time, since the reaction conditions are mild, the structure of the copper-iron bimetallic MOFs material will not be damaged, thus providing a new idea for the application of MOFs in catalysis.
[0061] In the present invention, the furan compound can be selected from a wide range. According to a preferred embodiment of the present invention, the furan compound is selected from at least one of 2-methylfuran, 2,5-dimethylfuran and furan, and is preferably a biomass-based furan compound.
[0062] In the present invention, the amine compound has a wide range of optional options. According to a preferred embodiment of the present invention, the amine compound is selected from at least one of aniline, p-methoxyaniline, 3-fluoroaniline, 3-methoxyaniline, m-toluidine, o-phenylenediamine, o-toluidine, n-butylamine, 3-nitroaniline, 4-nitroaniline, p-trifluoromethylaniline, p-chloroaniline, p-hydroxyaniline, n-hexylamine, furfurylamine, 2-thiophenemethylamine and benamine.
[0063] In the present invention, the liquid diluent may be selected from a wide variety of types. According to a preferred embodiment of the present invention, the liquid diluent is selected from at least one of anhydrous methanol, anhydrous ethanol, propanol, isopropanol, n-butanol, toluene, cyclohexane, dichloromethane, tetrahydrofuran, acetone, and methyl isobutyl ketone, preferably at least one of anhydrous methanol, isopropanol, tetrahydrofuran, and methyl isobutyl ketone.
[0064] In the present invention, the contact conditions of the furan compound, the amine compound and the catalyst can be selected in a wide range. According to a preferred embodiment of the present invention, the contact conditions include: a temperature of 100-220°C, preferably 120-200°C; the reaction time can be reasonably determined according to actual needs, and the reaction time is 1-24h, preferably 4-16h.
[0065] In the present invention, the mass ratio of the furan compound to the catalyst can be selected in a wide range. According to a preferred embodiment of the present invention, the mass ratio of the furan compound to the catalyst is 1-80:1, preferably 2-20:1.
[0066] In the present invention, the mass ratio of the furan compound to the amine compound can be selected in a wide range. According to a preferred embodiment of the present invention, the mass ratio of the furan compound to the amine compound is 1-300:1, preferably 5-100:1.
[0067] In the present invention, the mass ratio of the liquid phase diluent to the furan compound can be selected in a wide range. According to a preferred embodiment of the present invention, the mass ratio of the liquid phase diluent to the furan compound is 0-200:1, preferably 5-50:1.
[0068] In the present invention, the reaction product N-substituted pyrrole compound is analyzed qualitatively and quantitatively by gas chromatography-mass spectrometry (GC-MS), and the conversion rate of the product soluble carbohydrate is analyzed by high performance liquid chromatography (HPLC). The gas chromatography-mass spectrometer is Agilent 7890A of Agilent Corporation of the United States, the chromatographic column is HP-5 non-polar capillary column (30m, 0.53mm), the gas chromatograph is Agilent 7890B, the detector is hydrogen flame ionization detector (FID), and the chromatographic column is SE-54 capillary column (30m, 0.53mm). The high performance liquid chromatography adopts Agilent 1200 analysis, and the chromatographic column is SHODEX SC1011 sugar column (8×300mm).
[0069] In the present invention, the pyridine adsorption infrared method (Nicolet Model 710 spectrometer) is used to determine the amount of catalyst acid and the type of acid. The specific operating steps are as follows: a. Sample pretreatment. The sample (about 30 mg) is pressed into a thin disc with a diameter of 13 mm and loaded into an infrared sample tank. After that, the sample is pretreated for 1 hour under vacuum cell conditions and at 150°C. After the sample tank is cooled to room temperature, the sample infrared data is scanned as a background. b. Pyridine adsorption. At room temperature and vacuum environment, pyridine vapor is introduced into the original position until the adsorption reaches equilibrium, and the adsorption time is 1 hour. c. Pyridine desorption. After the adsorption is completed, evacuate at 100°C until the internal pressure no longer changes, the desorption time is 40 minutes, and the infrared absorption spectrum is scanned and recorded respectively. The difference spectrum before and after pyridine adsorption is the obtained pyridine adsorption-infrared absorption spectrum. The acid content of the sample is semi-quantitatively calculated according to the spectrum:
[0070]
[0071]
[0072] Where r and w are the diameter (cm) and mass (g) of the catalyst disc, A is the absorbance integral value at the specified wave number peak based on the scanning pyridine adsorption-infrared absorption spectrum, IMEC is the integrated molar extinction coefficient, IMECL is 2.22, and IMECB is 1.67.
[0073] In the present invention, the XRD measurement method of the bimetallic MOFs material is: the phase of the sample is analyzed by using a Rigaku Ultima IV X-ray powder diffractometer from Japan, and a CuKα ray source is used. Nickel filter, 2θ scanning range 3°-75°, operating voltage 35KV, current 25mA, scanning rate 10° / min.
[0074] In the present invention, the determination of surface element binding energy is carried out on an X-ray photoelectron spectrometer (ESCALAB-250) produced by Thermo Company, and C1s=284.6 eV is used as an internal standard to calibrate the measured element signal.
[0075] In the present invention, the inductively coupled plasma atomic emission spectrometer (ICP) model is Varian 725-ES, and the analysis sample is dissolved with hydrofluoric acid to detect the content of the element.
[0076] In the present invention, the furan compound conversion rate formula takes 2,5-dimethylfuran as the substrate as an example:
[0077] The conversion rate of 2,5-dimethylfuran (%) = (the molar amount of 2,5-dimethylfuran participating in the reaction) / (the molar amount of 2,5-dimethylfuran as the reaction substrate) × 100%.
[0078] The calculation formula for the yield of product N-substituted pyrrole is as follows, taking 2,5-dimethylfuran as the substrate:
[0079] The yield of the product N-substituted pyrrole (%) = (the molar amount of N-substituted pyrrole produced by the reaction) / (the molar amount of the reaction substrate 2,5-dimethylfuran) × 100%.
[0080] The selectivity of the product N-substituted pyrrole (%) = (molar amount of N-substituted pyrrole produced by the reaction) / (molar amount of 2,5-dimethylfuran reacted) × 100%.
[0081] In order to facilitate the understanding of the present invention, the present invention lists the following embodiments, but the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0082] Example 1
[0083] S1. Weigh 3g of trimesic acid (BTC) and add it to a mixture of 70mL of anhydrous ethanol and 40mL of DMF, and stir it thoroughly for 20min; weigh 6g of copper nitrate trihydrate and dissolve it in 70mL of H2O, then mix the two solutions, stir the mixture thoroughly and put it into a reactor, and crystallize it at 85℃ for 20h. After crystallization, cool it to room temperature, centrifuge to remove the mother liquor, and wash it with ethanol. Drying is carried out in two stages, the temperature of the first stage is 75℃, the time is 4h, and the drying temperature of the second stage is 130℃, the time is 10h. After drying, Cu-BTC is obtained.
[0084] S2, weigh 0.2g of ferrous sulfate and dissolve it in 20mL of water, then add 0.1g of iron powder, stir for 20min, add 80mL of ethanol, and stir for 20min to obtain an iron-containing solution. Weigh 2.0g of Cu-BTC prepared in step S1 and add it to the iron-containing solution, then place it in a water bath at 75°C and react for 6h. Then centrifuge to remove the mother liquor, wash it alternately with ethanol and water, and dry it to obtain Fe-Cu-BTC.
[0085] The SEM image of Cu-BTC is as follows Figure 1 As shown, it is a regular octahedral crystal with a smooth surface.
[0086] The SEM image of Fe-Cu-BTC is shown in Figure 2 As shown, it is a regular octahedral crystal, and the particles are attached to the crystal surface, showing a uniform network distribution.
[0087] The X-ray photoelectron spectroscopy (XPS) of Cu-BTC and Fe-Cu-BTC is shown in Figure 4. Cu-BTC has a peak at 935.0 eV, corresponding to Cu(II)2p 3 / 2, indicating that the Cu in the Cu-BTC structure exists in the form of Cu(II). After modification with ferrous sulfate and iron powder, a new characteristic peak appeared at 933.1eV in the Fe-Cu-BTC sample, corresponding to the Cu 2p of Cu(I). 3 / 2 Binding energy: The molar ratio of Cu(II) to Cu(I) is 1.18. The peaks of Fe-Cu-BTC at Fe 2p are 711.5eV and 726.2eV, which are 1.4eV and 2.5eV offset from the peaks of ferrous sulfate at 710.1eV and 723.7eV.
[0088] Pyridine desorption infrared images of Cu-BTC and Fe-Cu-BTC are shown in Figure 5 As shown. By pyridine desorption infrared Figure 5 The calculated total acid content of Cu-BTC is 64.2 μmol·g -1 The total acid content of Fe-Cu-BTC is 224.6 μmol·g -1 , and by Figure 5 It is found that Fe-Cu-BTC contains only L acid (Lewis acid).
[0089] From Figure 4 and Figure 5 The results show that the present invention provides a Fe-Cu-BTC metal organic framework (MOFs) material, in which both Fe and Cu metals form bonds with BTC organic ligands, and due to the interaction between the two metals, the valence state changes, forming more empty coordination sites. The pyridine desorption infrared image shows that the modified material Fe-Cu-BTC contains only L acid.
[0090] The Fe / Cu of the sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) and found to be 0.18 (molar ratio).
[0091] Depend on Figure 6 It can be seen that the characteristic peak positions of samples Fe-Cu-BTC and Cu-BTC are consistent, indicating that they have the same crystal form.
[0092] Example 2
[0093] S1. Weigh 3g of terephthalic acid (BDC) and add it to a mixture of 50mL of tetrahydrofuran and 60mL of water, and stir it thoroughly for 20min. Weigh 6g of copper nitrate trihydrate and dissolve it in 60mL of H2O, then mix the two solutions, stir the mixture thoroughly and put it into a reactor, and crystallize it at 85℃ for 20h. After crystallization, cool it to room temperature, centrifuge to remove the mother liquor, and wash it with ethanol. Drying is carried out in two stages, the temperature of the first stage is 75℃, the time is 4h, and the drying temperature of the second stage is 130℃, the time is 10h. After drying, Cu-BDC is obtained.
[0094] S2, weigh 0.2g of ferrous sulfate and dissolve it in 20mL of water, then add 0.1g of iron powder, stir for 20min, add 80mL of ethanol, and stir for 20min to obtain an iron-containing solution. Weigh 2.0g of Cu-BDC prepared in step S1 and add it to the above iron-containing solution, then place it in a water bath at 75°C and react for 6h. Then centrifuge to remove the mother liquor, wash it alternately with ethanol and water, and dry it to obtain Fe-Cu-BDC.
[0095] The SEM, XPS and XRD patterns of the Fe-Cu-BDC sample are similar to those of the Fe-Cu-BTC in Example 1. The Fe / Cu of the sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 0.15 (molar ratio). The molar ratio of Cu(II) to Cu(I) measured by XPS was 1.10. The Fe-Cu-BDC was measured by pyridine desorption infrared to contain only L acid, and the calculated L acid amount was 210.8 μmol·g -1 .
[0096] Example 3
[0097] The method of Example 1 is followed, except that in step S2, the content of ferrous sulfate added is 0.5 g, and the other conditions are the same as those of Example 1; Fe-Cu-BTC-3 is obtained.
[0098] The SEM, XPS and XRD patterns of the sample Fe-Cu-BTC-3 are similar to those of the Fe-Cu-BTC in Example 1. The Fe / Cu of the sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 0.21 (molar ratio). The molar ratio of Cu(II) to Cu(I) measured by XPS was 0.85. Fe-Cu-BTC-3 was measured by pyridine desorption infrared to contain only L acid, and the calculated L acid amount was 256.9 μmol·g -1 .
[0099] Example 4
[0100] The method of Example 1 is followed, except that in step S2, the content of iron powder added is 0.2 g, and the other conditions are the same as those of Example 1; Fe-Cu-BTC-4 is obtained.
[0101] The SEM, XPS and XRD patterns of the sample Fe-Cu-BTC-4 are similar to those of the Fe-Cu-BTC in Example 1. The Fe / Cu of the sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 0.24 (molar ratio). The molar ratio of Cu(II) to Cu(I) measured by XPS was 0.56. Fe-Cu-BTC-4 was measured by pyridine desorption infrared to contain only L acid, and the calculated L acid amount was 240.6 μmol·g -1 .
[0102] Example 5
[0103] The method of Example 1 is followed, except that in step S2, the reaction temperature of Cu-BTC and the iron-containing solution is 40° C., and the other conditions are the same as those of Example 1; Fe-Cu-BTC-5 is obtained.
[0104] The SEM, XPS and XRD patterns of the sample Fe-Cu-BTC-5 are similar to those of the Fe-Cu-BTC in Example 1. The Fe / Cu of the sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 0.13 (molar ratio). The molar ratio of Cu(II) to Cu(I) measured by XPS was 1.59. Fe-Cu-BTC-5 was measured by pyridine desorption infrared to contain only L acid, and the calculated L acid amount was 190.7 μmol·g -1 .
[0105] Example 6
[0106] The method of Example 1 is followed, except that in step S2, the reaction temperature of Cu-BTC and the iron-containing solution is 100° C., and the other conditions are the same as those of Example 1; Fe-Cu-BTC-6 is obtained.
[0107] The SEM, XPS and XRD patterns of the sample Fe-Cu-BTC-6 are similar to those of the Fe-Cu-BTC in Example 1. The Fe / Cu of the sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 0.15 (molar ratio). The molar ratio of Cu(II) to Cu(I) measured by XPS was 0.77. Fe-Cu-BTC-6 was measured by pyridine desorption infrared to contain only L acid, and the calculated L acid amount was 203.7 μmol·g -1 .
[0108] Example 7
[0109] The method of Example 1 is followed, except that in step S2, 0.2 g of ferrous sulfate is added instead of 0.2 g of ferrous sulfate, and the remaining conditions are the same as those of Example 1; Fe-Cu-BTC-7 is obtained.
[0110] The SEM, XPS and XRD patterns of the sample Fe-Cu-BTC-7 are similar to those of the Fe-Cu-BTC in Example 1. The Fe / Cu of the sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 0.11 (molar ratio). The molar ratio of Cu(II) to Cu(I) measured by XPS was 1.89. Fe-Cu-BTC-7 was measured by pyridine desorption infrared to contain only L acid, and the calculated L acid amount was 172.3 μmol·g -1 .
[0111] Example 8
[0112] The method of Example 1 is followed, except that in step S2, 0.2 g of ferrous chloride is added instead of 0.2 g of ferrous sulfate, and the remaining conditions are the same as those of Example 1; Fe-Cu-BTC-8 is obtained.
[0113] The XPS and XRD patterns of sample Fe-Cu-BTC-8 are similar to those of Fe-Cu-BTC in Example 1. Figure 3 As shown, the crystal is a regular octahedron with uniform particles distributed on the surface. The Fe / Cu of the sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 0.17 (molar ratio). XPS measured the molar ratio of Cu(II) to Cu(I) to be 1.28. Pyridine desorption infrared measured that Fe-Cu-BTC-8 only contained L acid, and the calculated L acid amount was 236.1 μmol·g -1 .
[0114] Example 9
[0115] The method of Example 1 is followed, except that in step S2, 0.2 g of ferric chloride is added instead of 0.2 g of ferrous sulfate, and the remaining conditions are the same as those of Example 1; Fe-Cu-BTC-9 is obtained.
[0116] The XPS and XRD patterns of the sample Fe-Cu-BTC-9 are similar to those of the Fe-Cu-BTC in Example 1. The SEM pattern is similar to that of the sample in Example 8. The Fe / Cu of the sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 0.10 (molar ratio). The molar ratio of Cu(II) to Cu(I) measured by XPS was 2.10. Pyridine desorption infrared measured that Fe-Cu-BTC-9 contained only L acid, and the calculated L acid amount was 175.9 μmol·g -1 .
[0117] Examples 10-18
[0118] With 2,5-dimethylfuran and aniline as substrates and methanol as reaction solvent, 0.2g of Fe-Cu-BTC-n or Fe-Cu-BDC in the above-mentioned embodiment 1-9, 1.5g of 2,5-dimethylfuran and 1.0g of aniline were stirred in a high pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The heating jacket was heated to the preset temperature by program heating, and then stirred by magnetic stirring. The reaction was carried out at 170°C for 10h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-dimethylfuran and the yield of the target product 2,5-dimethyl-1-phenylpyrrole, as shown in Table 1.
[0119] Table 1 Catalytic evaluation results of Examples 10-18
[0120]
[0121] Embodiment 19
[0122] The method of Example 10 was followed, except that 0.1 g of Fe-Cu-BTC prepared in Example 1 was used as a catalyst, and the other conditions were the same as in Example 10.
[0123] The conversion rate of 2,5-dimethylfuran was 99%, and the yield of N-substituted pyrrole compound was 98.3%.
[0124] Embodiment 20
[0125] The method of Example 10 was followed, except that 0.6 g of Fe-Cu-BTC prepared in Example 1 was used as a catalyst, and the other conditions were the same as in Example 10.
[0126] The conversion rate of 2,5-dimethylfuran was 98.2%, and the yield of N-substituted pyrrole compound was 97.5%.
[0127] Embodiment 21
[0128] With 2,5-dimethylfuran and aniline as substrates and methanol as reaction solvent, 0.2g of Fe-Cu-BTC in Example 1, 1.5g of 2,5-dimethylfuran and 1.0g of aniline were stirred in a high-pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to the preset temperature using a programmed heating jacket, and then stirred using magnetic stirring. The reaction was carried out at 140°C for 10h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-dimethylfuran and the yield of the target product 2,5-dimethyl-1-phenylpyrrole.
[0129] The conversion rate of 2,5-dimethylfuran was 95.9%, and the yield of N-substituted pyrrole compound was 96.1%.
[0130] Embodiment 22
[0131] With 2,5-dimethylfuran and aniline as substrates and methanol as reaction solvent, 0.2g of Fe-Cu-BTC in Example 1, 1.5g of 2,5-dimethylfuran and 1.0g of aniline were stirred in a high pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 190°C for 10h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-dimethylfuran and the yield of the target product 2,5-dimethyl-1-phenylpyrrole.
[0132] The conversion rate of 2,5-dimethylfuran was 99.6%, and the yield of N-substituted pyrrole compound was 92.3%.
[0133] Embodiment 23
[0134] With 2,5-dimethylfuran and aniline as substrates and methanol as reaction solvent, 0.2g of Fe-Cu-BTC in Example 1, 1.5g of 2,5-dimethylfuran and 1.0g of aniline were stirred in a high-pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 170°C for 15h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-dimethylfuran and the yield of the target product 2,5-dimethyl-1-phenylpyrrole.
[0135] The conversion rate of 2,5-dimethylfuran was 99.5%, and the yield of N-substituted pyrrole compound was 91.2%.
[0136] Embodiment 24
[0137] With 2,5-dimethylfuran and aniline as substrates and methanol as reaction solvent, 0.2g of Fe-Cu-BTC in Example 1, 1.5g of 2,5-dimethylfuran and 0.5g of aniline were stirred in a high pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The heating jacket was heated to a preset temperature using a programmed temperature increase, and then stirred using a magnetic stirrer. The reaction was carried out at 170°C for 10h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-dimethylfuran and the yield of the target product 2,5-dimethyl-1-phenylpyrrole.
[0138] The conversion rate of 2,5-dimethylfuran was 99.2%, and the yield of N-substituted pyrrole compound was 97.3%.
[0139] Embodiment 25
[0140] With 2,5-dimethylfuran and aniline as substrates and tetrahydrofuran as reaction solvent, 0.2g of Fe-Cu-BTC in Example 1, 1.5g of 2,5-dimethylfuran and 1.0g of aniline were stirred in a high pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The heating jacket was heated to a preset temperature using a programmed temperature increase, and then stirred using a magnetic stirrer. The reaction was carried out at 170°C for 10h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-dimethylfuran and the yield of the target product 2,5-dimethyl-1-phenylpyrrole.
[0141] The conversion rate of 2,5-dimethylfuran was 98.7%, and the yield of N-substituted pyrrole compound was 96.6%.
[0142] Embodiment 26
[0143] With 2,5-dimethylfuran and aniline as substrates and methyl isobutyl ketone as the reaction solvent, 0.2g of Fe-Cu-BTC in Example 1, 1.5g of 2,5-dimethylfuran and 1.0g of aniline were stirred in a high-pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to the preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 170°C for 10h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-dimethylfuran and the yield of the target product 2,5-dimethyl-1-phenylpyrrole.
[0144] The conversion rate of 2,5-dimethylfuran was 97.3%, and the yield of N-substituted pyrrole compound was 98%.
[0145] Embodiment 27
[0146] With 2-methylfuran and aniline as substrates and methanol as reaction solvent, 0.2g of Fe-Cu-BTC in Example 1, 1.5g of 2-methylfuran and 1.0g of aniline were stirred in a high pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 170°C for 10h, and the reaction solution was analyzed to obtain the conversion rate of 2-methylfuran and the yield of the target product 2-methyl-1-phenylpyrrole.
[0147] The conversion rate of 2-dimethylfuran was 97.4%, and the yield of N-substituted pyrrole compound was 97.8%.
[0148] Embodiment 28
[0149] With 2,5-dimethylfuran and aniline as substrates and methanol as reaction solvent, 0.2g of Fe-Cu-BTC in Example 1, 1.5g of 2,5-dimethylfuran, 0.5g of deionized water and 1.0g of aniline were stirred in a high pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 170°C for 10h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-dimethylfuran and the yield of the target product 2,5-dimethyl-1-phenylpyrrole.
[0150] The conversion rate of 2,5-dimethylfuran was 98.5%, and the yield of N-substituted pyrrole compound was 96.9%.
[0151] Embodiment 29
[0152] The method of Example 10 is followed, except that m-toluidine is used instead of aniline, and the other conditions are the same as Example 10.
[0153] The conversion rate of 2,5-dimethylfuran was 95.0%, and the yield of N-substituted pyrrole compound was 93.5%.
[0154] Embodiment 30
[0155] The method of Example 10 is followed, except that n-hexylamine is used instead of aniline, and the other conditions are the same as Example 10.
[0156] The conversion rate of 2,5-dimethylfuran was 93.8%, and the yield of N-substituted pyrrole compound was 90.1%.
[0157] Embodiment 31
[0158] The method of Example 10 is followed, except that p-methoxyaniline is used instead of aniline, and the other conditions are the same as those of Example 31.
[0159] The conversion rate of 2,5-dimethylfuran was 90.7%, and the yield of N-substituted pyrrole compound was 85.6%.
[0160] Comparative Example 1
[0161] With 2,5-dimethylfuran and aniline as substrates and methanol as reaction solvent, 0.2g HY(12), 1.5g 2,5-dimethylfuran and 1.0g aniline were stirred in a high pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by program heating, and then stirred by magnetic stirring. The reaction was carried out at 170℃ for 10h. The reaction liquid was analyzed to obtain a 2,5-dimethylfuran conversion rate of 63.4% and a target product 2,5-dimethyl-1-phenylpyrrole yield of 56.1%.
[0162] Comparative Example 2
[0163] With 2,5-dimethylfuran and aniline as substrates and methanol as reaction solvent, 0.2g sulfonated carbon, 1.5g 2,5-dimethylfuran and 1.0g aniline were stirred in a high pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The heating jacket was heated to the preset temperature by program heating, and then stirred by magnetic stirring. The reaction was carried out at 170℃ for 10h, and the reaction liquid was analyzed to obtain a 2,5-dimethylfuran conversion rate of 83.9% and a target product 2,5-dimethyl-1-phenylpyrrole yield of 73.7%.
[0164] Comparative Example 3
[0165] With 2,5-dimethylfuran and aniline as substrates and methanol as reaction solvent, 0.2g sulfonated carbon, 1.5g 2,5-dimethylfuran, 0.5g deionized water and 1.0g aniline were stirred in a high pressure reactor. 1MPa nitrogen was filled to prevent the organic solvent from boiling. The heating jacket was heated to the preset temperature by program heating, and then stirred by magnetic stirring. The reaction was carried out at 170℃ for 10h. The reaction liquid was analyzed to obtain a 2,5-dimethylfuran conversion rate of 60.5% and a target product 2,5-dimethyl-1-phenylpyrrole yield of 51.6%.
[0166] Comparative Example 4
[0167] The method of Example 10 was followed, except that 0.2 g of Cu-BTC prepared according to the method of Example 1 was used to replace 0.2 g of Fe-Cu-BTC prepared in Example 1, and the other conditions were the same as Example 10.
[0168] Analysis of the reaction solution revealed that the conversion rate of 2,5-dimethylfuran was 70.5%, and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 61.9%.
[0169] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A copper-iron bimetallic MOFs material, characterized in that: The copper-iron bimetallic MOFs material comprises: A bimetallic center formed by Fe and Cu containing two or more valence states; and Organic ligands that hybridize with the bimetallic center through coordination bonds to form a three-dimensional network structure crystal; The copper-iron bimetallic MOFs material contains only L acid and the amount of L acid is 100-600 μmol·g -1 .
2. The copper-iron bimetallic MOFs material according to claim 1, wherein: In the copper-iron bimetallic MOFs material, the amount of L acid is 150-400 μmol·g -1 .
3. The copper-iron bimetallic MOFs material according to claim 1 or 2, wherein: The organic ligand is selected from at least one of trimesic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 4,4,4-tris(N,N-di(4-carboxyphenyl)-amino)triphenylamine, 3,3,5,5-biphenyltetracarboxylic acid, imidazole, 2-methylimidazole, 2-nitroimidazole and 2-nitroimidazole derivatives; preferably at least one of trimesic acid and terephthalic acid; and / or In the copper-iron MOFs material, the metal Cu has two valence states, and preferably, the molar ratio of divalent Cu to monovalent copper is 0.01-5; and / or The molar ratio of metal Cu to metal Fe is (1-200):1, preferably (1-80):1; and / or The molar ratio of metal Cu to organic ligand is 0.1-10.
4. The copper-iron bimetallic MOFs material according to any one of claims 1 to 3, wherein: The copper-iron bimetallic MOFs material crystal is a polyhedral structure; and / or The copper-iron bimetallic MOFs material has a crystal size of 5-20 μm; Preferably, the crystal surface of the copper-iron bimetallic MOFs material presents a regularly rough or uneven morphology; More preferably, the rough morphology covers the surface of the copper-iron bimetallic MOFs material crystal in a network shape; or The rough morphology is in the form of particles covering the crystal surface of the copper-iron bimetallic MOFs material.
5. The method for preparing the copper-iron bimetallic MOFs material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1, dissolving the organic ligand and the Cu salt in a solvent, crystallizing, separating, and first drying to obtain a Cu-based MOFs material formed by Cu and the organic ligand; S2, contacting the Cu-based MOFs material in step S1 with a water-alcohol mixture containing Fe element and Fe salt; separating and performing a second drying to obtain the copper-iron bimetallic MOFs material.
6. The preparation method according to claim 5, wherein: In step S1, the crystallization conditions include: a crystallization temperature of 30-150° C.; and / or a crystallization time of 3-24 h; and / or In step S1, the first drying condition includes: a drying temperature of 70-200°C; and / or a drying time of 2-48h; and / or In step S2, the contact conditions include: a contact temperature of 30-150°C; and / or a contact time of 3-24h.
7. The preparation method according to claim 5 or 6, wherein: The Cu salt is selected from at least one soluble salt of metallic Cu; and / or The Fe salt is at least one selected from soluble salts of metallic Fe; and / or In step S1, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, triethylamine, hydrofluoric acid, tetrahydrofuran, methanol, ethanol and deionized water; and / or In step S2, in the water-alcohol mixture, the alcohol is selected from C1-C5 monohydric alcohol or polyhydric alcohol, preferably at least one of methanol, ethanol, propanol and ethylene glycol.
8. The preparation method according to claim 5, wherein: In step S1, the organic ligand is selected from trimesic acid and / or terephthalic acid; and / or In step S2, in the Fe salt, the anion is selected from at least one of chloride ion and sulfate ion.
9. The preparation method according to any one of claims 5 to 8, wherein: In step S1, the ratio of the solvent to the Cu salt is 5-100 mL of solvent / 1.0 g of Cu salt; and / or In step S2, the molar ratio of elemental Fe to soluble Fe salt is 1:0.1-10; In step S2, the dosage ratio of Fe salt is 5-200 mL solvent / 1.0 g.
10. Use of the copper-iron bimetallic MOFs material according to any one of claims 1 to 4 in the synthesis of pyrrole compounds.
11. A method for preparing an N-substituted pyrrole compound, characterized in that: The method includes: In the presence of a liquid diluent, a furan compound and an amine compound are contacted with a catalyst; the catalyst contains the copper-iron bimetallic MOFs material according to any one of claims 1-4.
12. The method according to claim 11, wherein: The furan compound is selected from at least one of 2-methylfuran, 2,5-dimethylfuran and furan, and is preferably a biomass-based furan compound; and / or The amine compound is at least one selected from aniline, p-methoxyaniline, 3-fluoroaniline, 3-methoxyaniline, m-toluidine, o-phenylenediamine, o-toluidine, n-butylamine, 3-nitroaniline, 4-nitroaniline, p-trifluoromethylaniline, p-chloroaniline, p-hydroxyaniline, n-hexylamine, furfurylamine, 2-thiophenemethylamine and benamine; and / or The liquid diluent is selected from at least one of anhydrous methanol, anhydrous ethanol, propanol, isopropanol, n-butanol, toluene, cyclohexane, dichloromethane, tetrahydrofuran, acetone, and methyl isobutyl ketone, preferably at least one of anhydrous methanol, isopropanol, tetrahydrofuran, and methyl isobutyl ketone.
13. The method according to claim 11 or 12, wherein: The contact conditions include: temperature of 100-220°C; reaction time of 1-24h; and / or The mass ratio of furanic compound to catalyst is 1-80:1; and / or The mass ratio of the furan compound to the amine compound is 1-300:1; and / or The mass ratio of the solvent to the furan compound is 0-200:1.
Citation Information
Patent Citations
MOFs dual-metal adsorption material (Fe, Co)-BTC and preparation method thereof
CN106076242A
Bimetallic center metal-organic framework material capable of enhancing Lewis acidity and preparation method thereof
CN108722488A
Preparation of Fe-MOF catalyst having rich Lewis acid sites and application of catalyst in desulfurization
CN108948366A
Method for preparing N-aryl pyrrole compound
CN111574424A
Method for maintaining security for sensitive information and apparatus using the method
KR102091388B1